CONTROL OF VIBRIOSIS BY USING TURMERIC-KALMEGH EXTRACT WITH DIFFERENT PERIOD TREATMENTS IN WHITELEG SHRIMP IN THE FLOATING NET-CAGES - Wahjuningrum, Dinamella; Effendi, Irzal; Miranti, Shavika; Umam, Khoirul; Abdullah, Taufiq (Indonesian Aquaculture Journal, 2024)
Whiteleg shrimp Penaeus vannamei cultured in marine floating net-cage systems are highly susceptible to stress and diseases caused by Vibrio harveyi. This study aimed to evaluate the effect of turmeric Curcuma longa and kalmegh Andrographis paniculata on the growth performance and immune system of whiteleg shrimp against V. harveyi infection. The study utilized a completely randomized design with treatments including control (C), one week (1W), two weeks (2W), and four weeks (4W) of supplementation. The challenge test consisted of C+, C-, 1W, 2W, and 4W treatments. Parameters observed included growth performance, immune response, and resistance to V. harveyi. Results showed that the combination of turmeric and kalmegh significantly improved final biomass, weight gain, specific growth rate, and feed conversion ratio compared to the control. Survival rates after challenge tests revealed the highest survival in the C- group (93.33 ± 5.77%), followed by treatment 4W (86.67 ± 11.55%), 2W (76.67 ± 20.82%), 1W (46.67 ± 35.12%), and the lowest in C+ (33.33 ± 26.46%) with significant differences (P < 0.05) across treatments. Immune responses, including total hemocytes, phagocytosis activity, phenoloxidase activity, and respiratory burst, were also significantly improved in the treatment groups compared to the positive control. In conclusion, the combination of turmeric and kalmegh (2:1 ratio, 6 mL/kg of diet) significantly enhances both growth and immune responses of whiteleg shrimp, offering a potential alternative to antibiotics for controlling vibriosis in shrimp aquaculture.